2016
DOI: 10.1186/s12889-016-3228-1
|View full text |Cite
|
Sign up to set email alerts
|

Do socio-cultural factors influence medical students’ health status and health-promoting behaviors? A cross-sectional multicenter study in Germany and Hungary

Abstract: BackgroundPhysical and mental health is important for coping with the high requirements of medical studies that are associated with a higher risk for severe stress, insomnia, smoking, harmful alcohol consumption and easier access to drugs. Health behaviors of medical students influence not just their own health but also the health of their future patients. We examined whether socio-cultural factors can explain differences in students’ health status and health-promoting behaviors.MethodsA multicenter cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…Our cross-sectional multicenter study used a self-administered questionnaire and was carried out at four Medical Faculties in Germany and Hungary (Technische Universität Dresden, Ludwig-Maximilians-Universität Munich, Semmelweis University Budapest and University of Pécs). The questionnaire development process and piloting of the study among medical students from different nationalities has been reported elsewhere [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our cross-sectional multicenter study used a self-administered questionnaire and was carried out at four Medical Faculties in Germany and Hungary (Technische Universität Dresden, Ludwig-Maximilians-Universität Munich, Semmelweis University Budapest and University of Pécs). The questionnaire development process and piloting of the study among medical students from different nationalities has been reported elsewhere [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this context, there are examined the effects of the gross domestic product growth rate as year-to-year percentage at market prices based on constant local currency (Granados, 2012;Renton et al, 2012;Reeves et al, 2013). Successively, the health expenditures variable demonstrates the total health expenditures as percentage of gross domestic product marked , which measures the final consumption of healthcare goods and services applied in the studies of van Baal & Wong 2012 , whereas alcohol consumption is associated with numerous harmful health and social consequences (Riemenschneider et al, 2016).…”
Section: Methodological Approachmentioning
confidence: 99%
“…SHS and unhealthy lifestyle among college students have become major public health concerns and a research focus worldwide [6,13,15]. In particular, researchers in Africa have paid little attention to cultural influences (contemporary or otherwise) on SRH and HPL among students [6,16]. Indeed, multiple studies have demonstrated that economic and demographic drivers of unhealthy behavior in specific groups of young people are mitigatable if identified and treated at an early stage [2,6].…”
Section: Introductionmentioning
confidence: 99%